New mixed-dark soliton solutions to the hyperbolic generalization of the Burgers equation - Dusuncelı, Faruk; Baskonus, Hacı Mehmet; Esen, Alaattin; Bulut, Hasan (My University, 2019)
In this paper, we apply the exponential function method to find mixed-dark, exponentialand singular soliton solutions in the hyperbolic generalization of the Burgers equation.We obtain some entirely new mixed singular and dark soliton solutions. Under thesuitable values of parameters, various dimensional simulations of results are plotted.Finally, we present a conclusion by giving novelties of paper.
Keywords: Fizik; Uygulamalı; Matematik